2021
DOI: 10.1055/s-0040-1718583
|View full text |Cite
|
Sign up to set email alerts
|

Data Collection during the COVID-19 Pandemic: Learning from Experience, Resulting in a Bayesian Repertory

Abstract: Background A novel pandemic disease offered the opportunity to create new, disease-specific, symptom rubrics for the homeopathic repertory. Objective The aim of this study was to discover the relationship between specific symptoms and specific medicines, especially of symptoms occurring frequently in this disease. Materials and Methods Worldwide collection of data in all possible formats by various parties was coordinated by the Liga Medicorum Homeopathica Internationalis. As the data came … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Rutten et al developed an innovative mathematical model that uses Bayes' theorem and homeopathic symptoms as prognostic factors to establish the relationship between specific homeopathic symptoms and the effectiveness of a specific HMP. 17 In this way, based on good case reports, homeopathic symptoms in materia medica and repertories can be systematically checked, confirmed, or rejected. This approach has recently been used, for example, to create a homeopathic repertory for the treatment of COVID-19 patients on the basis of casuistics.…”
Section: Scientific Tools and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rutten et al developed an innovative mathematical model that uses Bayes' theorem and homeopathic symptoms as prognostic factors to establish the relationship between specific homeopathic symptoms and the effectiveness of a specific HMP. 17 In this way, based on good case reports, homeopathic symptoms in materia medica and repertories can be systematically checked, confirmed, or rejected. This approach has recently been used, for example, to create a homeopathic repertory for the treatment of COVID-19 patients on the basis of casuistics.…”
Section: Scientific Tools and Methodsmentioning
confidence: 99%
“…This approach has recently been used, for example, to create a homeopathic repertory for the treatment of COVID-19 patients on the basis of casuistics. 17 This is based on case collections, a promising research model for the future to improve the validity and prescription safety of homeopathic materia medica and repertories. This innovative approach has many methodological advantages but requires basic statistical and methodological knowledge and interest on the part of the practitioner.…”
Section: Scientific Tools and Methodsmentioning
confidence: 99%
“…Previous research studies have dealt with challenges to data collection, and marginalization of vulnerable communities during the pandemic (Walker, Bailey, Churchill, and Peckham, 2021;Rutten et al, 2021). Many researchers have demonstrated how digital divide turned into marginalization of vulnerable communities (Barry, 2013;Wamuyu, 2017).…”
Section: B Digital Divide Double Marginalization and Challenges To Data Collectionmentioning
confidence: 99%
“…This response clearly indicates that coresearchers need to take a side, which would affect research validity. In relation to this trend,Rutten et al (2021) observe that lockdowns during the pandemic have affected ways of collecting data and conducting research.The coresearchers' bias is also manifested in the recurrent use of many negative lexicons that form the coresearchers' discourses about the Bagri community often resulting in discrimination against the community and posing challenges to data collection. The coresearchers usually deploy words and terminologies that typically characterize their biased views of the Bagri community.…”
mentioning
confidence: 99%
“…Data collections of COVID-19 treatments showed that only a few medicines, mostly those that were also used during the 'Spanish' flue, were frequently used, while more than a hundred were proposed, among others based on repertorisations. [2][3][4] This rectifies further exploration of the accessibility of homeopathic data and especially the effectiveness of the homeopathic repertory. Does the repertory indicate medicines that work and not medicines that do not work?…”
Section: Introductionmentioning
confidence: 99%